REVITALIZING LOCAL CULTURE IN SUSTAINABLE ECOTOURISM DEVELOPMENT IN THE DIGITAL ERA - Sugiharto, Sugiharto (MSJ : Majority Science Journal, 2025)
This study aims to analyze the role of local cultural revitalization and the use of digital technology in supporting sustainable ecotourism development. A qualitative approach with a case study design was used in this research, which was conducted in Penglipuran Village (Bali) and Nglanggeran Village (Yogyakarta) from March to May 2025. Data were collected through in-depth interviews, participant observation, and documentation studies, then analyzed using thematic analysis techniques. The results indicate that revitalized local culture, such as traditional art performances, crafts, and local mythological narratives, plays a significant role in strengthening destination identity and creating educational tourism experiences. The use of digital technologies, such as social media, village websites, and audiovisual content, enables local communities to promote their culture more widely and independently. The younger generation plays a role as content creators and bridges between generations in cultural preservation. The integration of culture and digitalization has been proven to increase tourism competitiveness and encourage the empowerment of a locally-based creative economy. However, challenges such as the risk of cultural commodification and low digital literacy remain obstacles that need to be addressed collaboratively. This study emphasizes the importance of a participatory and culturally sensitive approach in ecotourism development in the digital era.